Pengaruh Brand Trust Dan Brand Image Terhadap Keputusan Pembelian Sepeda Motor Merek Honda Scoopy Di PT. Tunas Dwipa Matra Mojosari - Anik Musayadah; Nersiwad Nersiwad; Budi Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine how much influence brand trust and brand image have on purchasing decisions of Honda Scoopy motorcycles at PT. Tunas Dwipa Matra Mojosari. This type of research is quantitative research. The data analysis used in this study is PLS (Partial Least Square). The population in this study were all consumers who had purchased a motorcycle at PT. Tunas Dwipa Matra. The sample of this research is 100 respondents calculated using the slovin formula. The sampling technique uses a non-probability sampling technique, namely purposive sampling. The results of this study show that brand trust has a significant positive effect on purchasing decisions for Honda Scoopy motorcycles at PT. Tunas Dwipa Matra Mojosari. Brand image has a significant positive effect on purchasing decisions of Honda Scoopy motorcycles at PT. Tunas Dwipa Matra Mojosari.